The Relationship Model of Sharia and Financial Authorities - Muhammad Maksum (AHKAM : Jurnal Ilmu Syariah, 2020)
Political economy and religious policies affect the relationship between sharia and financial authorities. Countries that make Islam as the official religion put Sharia authorities within the scope of the state. Malaysia is one of the countries that put Sharia authorities in the structure of state authority, although it is subject to independency. In the meantime, Indonesia combines the two models of relationship: 1) granting broader independence to sharia authority (the Indonesian Ulema Council) and 2) forming sharia board to deal with sharia finance, among others. The comparison of Indonesian, Malaysian, and the Middle Eastern countries’ system shows that the independence and the effectiveness of sharia economic fatwa application are found to attract each other. This, in turn, influences the supervision of Islamic financial institutions.  AbstrakPolitik ekonomi dan kebijakan agama memengaruhi hubungan antara otoritas syariah dan otoritas keuangan. Negara yang menjadikan Islam sebagai agama resmi menempatkan otoritas syariah dalam ruang lingkup negara. Malaysia adalah salah satu negara yang menempatkan otoritas Syariah dalam struktur otoritas negara, meskipun tetap independen. Sementara itu, Indonesia menggabungkan dua model hubungan: 1) memberikan independensi yang lebih luas kepada otoritas syariah (Majelis Ulama Indonesia) dan 2) membentuk dewan syariah untuk menangani hal yang berkaitan dengan keuangan syariah. Perbandingan sistem Indonesia, Malaysia, dan negara-negara Timur Tengah menunjukkan bahwa independensi dan efektivitas penerapan fatwa ekonomi syariah terbukti saling berhubungan satu sama lain. Ini, pada gilirannya, memengaruhi pengawasan lembaga keuangan Islam.